Self-organised synthesis of Rh nanostructures with tunable chemical reactivity - Buatier de Mongeot, F (Springer, 2007)
Nonequilibrium periodic nanostructures such as nanoscale ripples, mounds and rhomboidal pyramids formed on Rh(110) are particularly interesting as candidate model systems with enhanced catalytic reactivity, since they are endowed with steep facets running along nonequilibrium low-symmetry directions, exposing a high density of undercoordinated atoms. In this review we report on the formation of these novel nanostructured surfaces, a kinetic process which can be controlled by changing parameters such as temperature, sputtering ion flux and energy. The role of surface morphology with respect to chemical reactivity is investigated by analysing the carbon monoxide dissociation probability on the different nanostructured surfaces.